EJI Equal Justice Initiative of Alabama - Equal Justice Initiative of Alabama (Organization) ([S.l. : s.n.)
Welcome to the official online resource of Equal Justice Initiative of Alabama, a non-profit organization that provides legal representation to indigent defendants and prisoners who have been denied fair and just treatment in the legal system. Come and explore how EJIA works with communities and litigates on behalf of condemned prisoners, juvenile offenders, people wrongly convicted or charged with violent crimes, poor people denied effective representation, and others whose trials are marked by racial bias or prosecutorial misconduct. The site also contains reports, newsletters, and manuals, and information on ways you can help.
Representation of death row prisoners -- Legal assistance to poor people -- Race and the criminal justice system -- Community education and reform -- Legal resource materials -- EJI staff -- How you can help -- Links to other sites -- Recent developments -- EJI's fight to free innocent death row prisoner -- 2004 report.
Title from title screen (viewed May 4, 2007).
Text in HTML and JavaScript; images in GIF and JPEG.
Postsecondary.
Mode of access: World Wide Web.
System requirements: Adobe Flash Player.
Keywords: Equal Justice Initiative of Alabama (Organization); Equality before the law -- United States; Justice, Administration of -- United States